Identification of sortase A (SrtA) substrates in Streptococcus uberis: evidence for an additional hexapeptide (LPXXXD) sorting motif - Egan, Sharon A.; Kurian, Dominic; Ward, Philip N.; Hunt, Lawrence; Leigh, James A. (American Chemical Society, 2009)
Sortase (a transamidase) has been shown to be responsible for the covalent attachment of proteins to the bacterial cell wall. Anchoring is effected on secreted proteins containing a specific cell wall motif toward their C-terminus; that for sortase A (SrtA) in Gram-positive bacteria often incorporates the sequence LPXTG. Such surface proteins are often characterized as virulence determinants and play important roles during the establishment and persistence of infection. Intramammary infection with Streptococcus uberis is a common cause of bovine mastitis, which impacts on animal health and welfare and the economics of milk production. Comparison of stringently produced cell wall fractions from S. uberis and an isogenic mutant strain lacking SrtA permitted identification of 9 proteins likely to be covalently anchored at the cell surface. Analysis of these sequences implied the presence of two anchoring motifs for S. uberis, the classical LPXTG motif and an additional LPXXXD motif.